Morphometric characterization of the Igarapé Carrapato river basin, Boa Vista, Roraima - Faria, Maola Monique (2017)
Watershed management is based on a set of techniques applied in order to regulate the flow of water resources, economic production and environmental protection, ensuring the preservation of biodiversity. This study aims to determine the morphometric characteristics of the Igarapé Carrapato river basin, Boa Vista - Roraima. Initially, we obtained the Digital Elevation Model and, based on that, the basin was delineated. Later some morphometric parameters were calculated for the study of the hydrological behavior of the basin. Based on analysis of the analyzed morphometric factors, the basin investigated in this study presents low susceptibility to flooding.